Analyzing The Continued Use Of Digital Banking In Generation Z Through Satisfaction Based On E-Servqual With E-Word Of Mouth As Moderation (Case Study In Tasikmalaya City) - Rahmawati, Mira; San Marino, Wilman; Hidayat, Deny; Santosa, Allicia Deana (SEAN Institute, 2024)
Consumers who are satisfied with their consumption of a particular good/service are highly likely to continue using that good/service. However, word of mouth, whether positive or negative, offline or electronic, will undoubtedly influence the intention to reuse digital banking services. This study aims to analyze and understand how e-servqual affects satisfaction and how e-WOM moderates the impact of satisfaction on the reuse of digital banking. The study employs a survey method by distributing questionnaires to 185 respondents selected through purposive random sampling. The analytical tool used in this research is Structural Equation Modelling (SEM), with e-servqual/electronic service quality as the independent variable and satisfaction and continuance intention as the dependent variables, and e-Word of Mouth as the moderating variable. Hypotheses are tested using the SmartPLS 3.2.9 program. The results of this study indicate that there is a significant influence of electronic service quality on satisfaction. There is also an influence between satisfaction and continuance intention, but e-WOM cannot moderate satisfaction on reuse intention. Therefore, it can be concluded that when consumers are already satisfied with digital banking services, they will continue to use digital banking despite reading many positive and negative reviews or opinions about digital banking.